Faktor yang Berhubungan dengan Penggunaan Obat Herbal dan Gambaran Biaya dalam Meningkatkan Kesehatan Masyarakat di Desa Magalau Hulu Kabupaten Kotabaru Kalimantan Selatan - Devi Nurvia Rahmawati; Melviani Melviani (BORNEO JOURNAL OF PHARMASCIENTECH, 2022)
Lifestyle back to nature is still widely used by the public, especially for the use of herbal medicine (plants). The most underlying reason society prefers the use of herbal remedies for treatment because it is believed to have no side effects such as chemical drugs and more affordable prices. Purpose : The purpose of this study was to determine the costs and factors associated with the use of herbal medicine in the community of Magalau Hulu Village, Kotabaru Regency, South Kalimantan.Metode : The method used in this study is to use the cross sectional method . Result : The result obtainde from of 57 respondents there were 37 people who took herbal medicine. Variables related to the use of herbal medicines in improving public health are information (p = 0.000) and distance (p = 0.000), as well as unrelated income (p= 0.223), for the costs incurred by the public to buy more herbal medicines with a range of < Rp 250,000. Conclusion : Based on the research that has been done, it is found that the factors related to information and distance, while the costs incurred by the community to buy herbal medicines are more in the range of < Rp 250,000.